Determination of the median effective dose (ED50) of spinal chloroprocaine in labour analgesia. (19th January 2017) - Coppens, M.; Anssens, S.; Parashchanka, A.; Roelens, K.; Deschepper, E.; De Hert, S.; Wouters, P. F.
Summary: The primary goal of this study was to determine the median effective dose (ED50 ) of spinal chloroprocaine for labour analgesia. Thirty‐eight parturients requesting neuraxial analgesia were enrolled. Doses of 1% chloroprocaine were determined by the technique of up–down sequential allocation, with an initial dose of 20 mg and steps of 2 mg. The chloroprocaine spinal dose was given as the spinal component of a combined spinal‐epidural, which was then supplemented with an epidural dose of 7.5 μg sufentanil in 7 ml saline. Effective analgesia was defined as a score ≤ 10 mm within 15 min on a 100‐mm visual analogue pain scale. Using the isotonic regression estimator method, the ED50 of chloroprocaine for the spinal component of a combined spinal‐epidural for labour was calculated to be median (95%CI) 12.0 (9.3–17.0) mg.